Center-level Utilization of Hepatitis C Virus–positive Donors for Orthotopic Heart Transplantation. Issue 12 (22nd November 2021) - Huckaby, Lauren V.; Seese, Laura M.; Handzel, Robert; Wang, Yisi; Hickey, Gavin; Kilic, Arman
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The use of hepatitis C virus–positive (HCV+) donors has expanded the donor pool for orthotopic heart transplantation (OHT). This study evaluated center-level trends and utilization of HCV+ donors for OHT. Methods: Data were extracted from the Scientific Registry of Transplant Recipients on adults (≥18 y) undergoing OHT between January 1, 2016 and December 31, 2019. Centers performing <10 OHTs during the study period were excluded. Donor utilization rates were evaluated at the center level. Center-level characteristics were compared between centers performing HCV+ donor hepatitis C virus–negative (HCV−) recipient OHTs and those not utilizing HCV+ donors for HCV− recipients. Results: A total of 10 134 patients underwent OHT, including 613 (6.05%) HCV+ donors transplanted into HCV− recipients. The number of HCV+ OHTs increased from 15 of 2512 (0.60%) in 2016 to 285 of 2490 (11.45%) in 2019 ( P < 0.001). In 2016, among 105 centers performing OHTs, 7 (6.67%) utilized HCV+ donors compared to 2019 during which 55 (52.89%) of 104 centers utilized HCV+ donors ( P < 0.001). In total, 57 of 107 (53.27%) centers utilized HCV+ donors during the study period. Centers utilizing HCV+ donors had higher overall donor utilization rates (7376/24 378 [30.26%] versus 3463/15 335 [22.58%], P < 0.001) and were higher volume as compared to nonutilizing centers (mean annual OHT volume 30.72 ± 1.21 versus 16.2 ± 1.40, P < 0.001). Conclusions: Although the use of HCV+ donors for OHT is rapidly expanding in the United States, almost half of transplant centers remain nonutilizers. Broader education and implementation of HCV+ donor protocols may be important in expanding OHT to more patients with end-stage heart failure. Abstract :